Anti-PGL1 salivary IgA/IgM, serum IgG/IgM, and nasal Mycobacterium leprae DNA in individuals with household contact with leprosy - Cabral, Paula Brito e (2013)
Objectives: Leprosy household contacts represent a group at high risk of developing the disease. The aim of this study was to detect Mycobacterium leprae subclinical infection in this group through serological and molecular parameters. Methods: Serum anti-PGL1 IgG/IgM and salivary anti-PGL1 IgA/IgM was investigated using an ELISA, and nasal carriage of M. leprae DNA was detected by PCR, in leprosy household contacts of paucibacillary (PB) and multibacillary (MB) household leprosy patients (n = 135), their index cases (n = 30), and in persons living in a low endemic city (n = 17). Results: Salivary anti-PGL1 IgA and IgM and serum anti-PGL1 IgG showed good correlation comparing contacts and index cases (p < 0.01, p < 0.005, and p < 0.0001, respectively). This was not observed for serum anti-PGL1 IgM (p > 0.05). A high frequency of anti-PGL1 IgM positivity was found in IgG-negative samples (p < 0.0001). For IgG-positive samples, IgM antibodies were also positive in most of the samples. None of the 17 volunteers living in a low endemic city presented seropositivity for IgG; however, two of them showed positivity for anti-PGL1 IgM. M. leprae DNA was found in the nasal swabs of nine out of the 85 MB household leprosy contacts (10.6%) and in three out of the 50 PB household leprosy contacts (6.0%). Conclusion: We strongly suggest that serum IgG/IgM and salivary anti-PGL1 IgA/IgM measurements are used to follow leprosy household contacts.